A atuação médica humanizada na promoção da saúde do paciente como fator contributivo para a racionalização da judicialização da saúde - Lima, Andréia Maura Bertoline Rezende de (2017)
The fundamental social right to health, which is inseparable from the right to life, must receive the protection of the State through health promotion, whose prevention of diseases is inserted in the strategies and guidelines articulated to promote a decent quality of life and social well-being. To promote health is to promote the improvement of the living conditions of citizens, considering the peculiarities and priorities of the community, inserted in a systemic context of integration with the public and private sectors, which must allocate resources with rationality and efficiency, giving priority to meeting the interests of the collectivity. Health care begins with conception and must accompany all stages of life until its termination. It is a continuous process of individual and collective education and motivation directed to the co-responsibility of each individual for the lifestyle choice, within the context of the environment in which it is inserted, respecting its autonomy, beliefs, and moral values. Based on the dignity of the human person, health promotion is directed at primary care, which consists in meeting the vital needs of the person, aiming at the universal access to health services or appropriate treatment, with equity and efficiency, in the face of the diagnosed disequilibrium. The patient is not a mere object of scientific study and of the latest technology. The doctor, for his part, is not just a technician with scientific knowledge and skills to treat the patient. Starting from the promotion of health through the primary care, we analyze the clinical encounter of the patient with the physician, the main protagonists of an interpersonal relationship that cherishes life, has solidarity with others, and welcomes a vulnerable and fragile being facing the unknown. It is at this moment that humanized medical care, centered on the patient's person and not on his pathology, is a contributory factor to the rationalization of health judicialization, the subject of this analytical and reflexive study, whose legal basis is the right to health and to life with dignity. Rationalizing the judicialization of health is not restricted only in the criticism of the judicial control of public health policies and compliance with the procedures of the National Supplementary Health Agency (ANS). Rationalizing the judicialization of health consists, above all, in the valuing of the human being in its entirety, establishing with it a relationship of empathy, trust and dialogue